Revitalising Naxi dongba as a 'pictographic' vernacular script. (March 2019) - Poupard, Duncan
A script can be a window into a language and all the culture contained within it. China's minority peoples have a multitude of scripts, but many are in danger of falling out of use, a decline spurred by the adoption and promotion of standard Chinese across the country. Nevertheless, efforts are being made to preserve minority writing systems. This article reveals how the primarily logographic Naxi dongba script (often labelled the world's 'last living pictographs'), used in China's southwestern Yunnan province to record the Naxi language, can be practically used as a modern writing system alongside its more widely known traditional role as a means of recording religious rites, and what exactly separates these two styles of writing. The efforts that have been made to achieve the goal of modernisation over the past decades are reviewed, including the longstanding attempts at Unicode encoding. I make some suggestions for the future development of the script, and employ plenty of examples from recent publications, alongside phonetic renderings and English translations. It is hoped that overall awareness of this unique script can be raised, and that it can develop into a vernacular script with everyday applications.